2021
DOI: 10.22271/fish.2021.v9.i4c.2538
|View full text |Cite
|
Sign up to set email alerts
|

Value chain analysis of dry fish marketing in coastal belt of Bangladesh

Abstract: Dried fish marketing plays an important role in the economy of Bangladesh, contributing to increased gross domestic product, diversification of the economy and increased employment opportunities. The aim of this study to examine the existing marketing system, identify different marketing channel and to estimate the value addition of different actors who are involved in the marketing chain of dry fish. Multistage stratified simple random sampling technique has been used in selecting the sample and the total 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Several studies have reported the microbial diversity of the surface and sub-surface regions of BoB 13 , 20 , 21 , but no comprehensive study has been performed yet on this important ecological system. These coastal regions of Bangladesh play an important economic role because they are the most visited tourist destination in the country 22 , 23 and the largest source of fisheries-based rural markets, supplying a significant portion of the country's fish 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the microbial diversity of the surface and sub-surface regions of BoB 13 , 20 , 21 , but no comprehensive study has been performed yet on this important ecological system. These coastal regions of Bangladesh play an important economic role because they are the most visited tourist destination in the country 22 , 23 and the largest source of fisheries-based rural markets, supplying a significant portion of the country's fish 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the types of value chains, number of actors, their roles, pricing mechanisms, and information sources are highly diversified based on the geographical areas, marketing systems, intermediaries (Nurhaliza, 2022), market types, product types (Mandal, 2021) and many more. Further, the efficient pricing information is not transmitted to the producers and traders through the marketing channel as a result of processors' lack of specialization to competitive advantage (Kayikci et al, 2022).…”
Section: Geographical Pricingmentioning
confidence: 99%
“…The value chain is a collection of actions that adds value to a product at every step of the process, from sourcing to manufacture, distribution, and final consumption (Mandal, 2021;Kaplinsky & Morris, 2001). In its most basic form, a value chain is condensed to fundamental operations such as production, value additions, wholesaling, and retailing, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its significant importance in terms of revenue and employment, the dry fish industry in Bangladesh has not received adequate attention, particularly in terms of research and management. Limited studies have been conducted on this industry, indicating a gap in understanding the distribution channel of dry fish (Ahmed, 1993;Amin et al, 2012;Marine et al, 2014;Mandal, 2021). Though dry fish market differs by regions, the distribution channels were found to be complex throughout the country (Amin et al, 2012;Marine et al, 2014).…”
Section: Introductionmentioning
confidence: 99%